Implementation of Marine Fishery Information System Model for The Increasing of Fisherman Prosperity (Case of Study: Pameungpeuk District, Garut City) - Putri Rudiawan, Amanda; Windupranata, Wiwin; Wisayantono, Dwi (Indonesian Journal of Geospatial, 2012)
Abstract. This research bring together the development and implementation of marine fishery information system model and study of up and down stream component that are indicated have significant impact for the increasing of fisherman prosperity in Cilauteureun fishery port (PPP Cilauteureun), Pameungpeuk. The model results a daily potential fishing zone (ZPPI) map that was distributes to the fisherman. Most of the fisherman in Cilauteureun are labor fisherman who have salary that is lower than the minimum regional salary/UMR (44% of UMR). Developed ZPPI maps contain information about the location of potential fishing zone, fishing route and distance, time and capital needed, and additional information about current, wind, and wave height. Operational cost efficiency resulted from the utilization of the ZPPI maps are 54% respectively for the small capacity vehicle/MT (less than 10 GT) and 41% respectively for bigger vehicle/KM (10-15 GT capacity). The efficiency also cause the MT labor fisherman salary increaing up to 219% (achieve 98% of UMR). The integration of upstream components (ZPPI maps, vehicles and equipments facility, and human resource quality) and downstream components (catchment result sales, traetment, and distribution system) also has important role for the prosperity progress of Cilauteureun local fisherman.Keywords: fishery information system, fisherman prosperity, fisherman salary increasing, fishing zone map, operational cost efficiency, PPP Cilauteureun.